Women's Refuge clients' experiences of social responses to domestic violence including interventions informed by response-based practice : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Wellington, New Zealand - Reedy, Jessica Juliet (Massey University, 2018)
In Aotearoa New Zealand, transformation in thinking about and acting to prevent domestic violence is exigent. Response-Based Practice (RBP) provides a transformational framework for ethical social responses for families experiencing violence. RBP attends to ways discursive practices undermine or support victim safety and dignity. The current research involved developing, delivering, and evaluating a RBP group intervention at Women's Refuge. Evaluation privileged women's accounts of the intervention and entailed comparing discourses clients utilised to inform their understandings of violence and position themselves before and after Group participation. Implications of clients' positioning for enabling or constraining their safety and dignity are also considered. The project's design used feminist collaborative action research principles, and thematic analysis in the first study to develop the intervention. Five advocates were engaged in meetings, semi-structured interviews, document reviews, and focus groups. The second study used discourse analysis of women's pre- and post- intervention accounts of their domestic violence experiences and social responses to them. Four clients engaged in semi-structured interviews. Before Group participation, discourses that minimised and mutualised violence predominated, positioning victims as instrumental in provoking and preventing violence, and victims and perpetrators as pathological. Languaging often represented perpetrators' violence as accidental/uncontrollable and concealed victim resistance. Narratives engaged traditional gender discourses of men's dominance, encompassing coercive control and violence, and women's submission and self-sacrifice, as normative. Women's entrapment by victim-blaming discourses alongside threats of poverty and condemnation from perpetrators, families, church and social agencies was evident. Following Group participation, resistance discourses prevailed. Clients challenged their positioning as pathological or blameworthy and re-positioned themselves as sensible, competent women. Group content and processes were constituted as privileging and legitimating women's unarticulated knowledge of how concealing violence, perpetrator responsibility and gendered social power relations diminish victims' safety. Narratives of domestic violence evinced increased recognition of patterns of coercive control, entrapment and other non-assaultive violence intersecting with harmful social responses and structural violence. Thus, the Group provided a safe and dignifying social and physical space for clients to collectively reconsider their responses to violence; and discover, discuss, and critique discursive practices that reveal violence, perpetrator responsibility, and victim resistances.
Listed in 2018 Dean's List of Exceptional Theses
Keywords: Abused women; New Zealand; Interviews; Women volunteers in social service; Victims of family violence; Services for; Women's shelters; Group psychotherapy; Dean's List of Exceptional Theses